A study on factors that influencing the attitude towards home financing among KL Airport Services (KLAS) Sepang, Selangor, Malaysia / Nurul Wahidah Abd Aziz and Siti Nur Balqis Ma’arof - Abd Aziz, Nurul Wahidah; Ma’arof, Siti Nur Balqis (2014)
The purpose of this research is to study the factors that influencing the attitude toward home financing among KL Airport Services (KLAS) Sepang, Selangor, Malaysia. The study has been carried out at KL Airport Services (KLAS). It involve 7 department in KLAS which are finance department, business and development department, purchasing and document department, human resources department, information system department, in-flight catering department and cargo department. The objectives of this research is to identify the relationship between bank reputation and employee’s attitude toward home financing, the relationship between price of the house and employee’s attitude toward home financing, the relationship between place of the house and employee’s attitude toward home financing and lastly the relationship between family and employee’s attitude toward home financing. The simple random sampling technique has been used to select the respondent from the sampling frame of these seven departments in KLAS. The overall result of the data analysis suggest that bank reputation, price of the house, family and place of the house have significant relationship towards the employee’s attitude toward home financing.